2015
DOI: 10.15761/docr.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic management of palatal perforation in heroin abuse patient

Abstract: Heroin induced palatal perforation is a very infrequent complication. The authors report in this study a patient who suffered palatal perforation as a result of long time of snorting Heroin. He presented complaining of liquid passage from the oral cavity into the nasal cavities and hypernasality during speech. An immediate transparent acrylic partial obturator was constructed and fitted. It was successful in sealing the defect. However after 4 months an enlargement in the perforation was evident due to failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some centers inform the patient that he will not be able to come for reevaluation if he continues drug abuse (Goodger et al 2005). In the literature it is reported that a therapeutic choice is the delay of the surgical restoration for about a year up to 18 months, in order to monitor, stabilize the patient and treat the possible inflammation with antibiotics (Peyriere et al 2013, El Charkawi andNasar, 2015). The cessation of abuse is verified through lab tests, such as urine test (Colletti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some centers inform the patient that he will not be able to come for reevaluation if he continues drug abuse (Goodger et al 2005). In the literature it is reported that a therapeutic choice is the delay of the surgical restoration for about a year up to 18 months, in order to monitor, stabilize the patient and treat the possible inflammation with antibiotics (Peyriere et al 2013, El Charkawi andNasar, 2015). The cessation of abuse is verified through lab tests, such as urine test (Colletti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The final treatment choice depends on the location and the dimensions of the lesion, the daily dose, the duration of drug abuse as well as the presence of local infections (Di Cosola et al 2007). Treatment includes two main choices: 1) the conservative approach with the fabrication of temporary or permanent removable prosthetic devices/obturators and 2) the surgical restoration of the perforation with the use of various flaps (El Charkawi and Nasar, 2015, Goodger et al 2005, Di Cosola et al 2007. Removable prosthetic devices are mainly temporary solutions of sealing the palate until the surgical restoration, as well as in cases where the patient refuses surgical treatment.…”
Section: πίνακαςmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Another temporary option that is available is the positioning of a silicone button to close the perforation and thus improve the air flow in the nose and reduce progression of local necrosis. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…7 Repeated injuries of the septum can lead to structure disruption and replacement with fibrous tissue. 7 As long as forensic pathology is performed with toxicological analyses in only selected cases and as long as drug users try to hide bodily consequences of their addiction, 10 identifying suspicious lesions such as septum defects that may be indicative of cocaine abuse is relevant.…”
mentioning
confidence: 99%